HEALTH BELIEF MODEL PERCEPTIONS OF MALAYSIAN ADULT E-CIGARETTE USERS: A GENDER ANALYSIS - Chin, Christina; Amer Nordin, Amer Siddiq; Thambiah, Shanthi; Somiah, Vilashini (SARJANA, 2025)
This study uses the Health Belief Model (HBM) as a tool to answer two research questions: 1) Are there differences in HBM perceptions based on the gender of Malaysian adult e-cigarette users? ; 2) Do gender norms influence e-cigarette use in Malaysia? A survey of 280 Malaysian adult e-cigarette users was conducted. Overall, gender did not have a statistically significant effect on 14 of the HBM perception statements analysed. The chi-square test showed that gender had a significant influence on two of the perception statements, while the ordered logit regression analysis revealed statistically significant differences in three of the perception statements. The implication of these findings on future public health policy aiming to reduce smoking prevalence in Malaysia must take into account the narrowing gender gap in relation to the use of e-cigarettes and the rising popularity of these nicotine delivery devices, particularly among youth.